1967
DOI: 10.1063/1.1709300
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength of Grossly Deformed Cu, Ag, and Au at High Pressures and Temperatures

Abstract: The shear strength of grossly deformed cop~er, silver, and gold has been meas~red ~n an opposed anvil shear apparatus at pressures up to 150 khar m the temperature ran?e from ~7 -900 C. Th~ shear data agree with independent strength measurements at low pressures, but differ. sigmfican~l:l:' from high-press~re shear strength measurements by other investigators. The data also fit a SImple empmcal formula relatmg the temperature and pressure dependence of the shear strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…15,16 This correlation between friction and silver content can be attributed to the fact that silver facilitates sliding over a range of temperatures due to its low shear strength. 17 We also observed that AgTaO 3 exhibited the lowest friction, slightly lower even than that of the Ta 2 O 5 /Ag film with similar silver content (i.e., 20%), which is consistent with our experimental results.…”
supporting
confidence: 82%
“…15,16 This correlation between friction and silver content can be attributed to the fact that silver facilitates sliding over a range of temperatures due to its low shear strength. 17 We also observed that AgTaO 3 exhibited the lowest friction, slightly lower even than that of the Ta 2 O 5 /Ag film with similar silver content (i.e., 20%), which is consistent with our experimental results.…”
supporting
confidence: 82%
“…[202] The resulting d min = 17.9 nm, the s max = 1.11 GPa, and via MacKenzie's crystal shear model (s max = G/30), with G = 45 GPa, s max = 1.5 GPa. These values appear to be overestimates when compared with experimentally determined maximum shear strengths from rotational diamond anvil cell studies (~100 to 500 MPa), [203] but the smallest predicted grain size of 17.9 nm, and the steady-state experimentally observed values from high-pressure torsion (~35 nm), [204] by cryomilling with no exposure to the liquid (~23 nm) [205] and by cryomilling with exposure to the liquid nitrogen (~24 nm) [206] could be said to ''be in general agreement.'' So where does this bring us in terms of estimating the smallest grain size and its role on strengthening?…”
Section: ½7mentioning
confidence: 62%
“…Nevertheless, the curve Y d (σ 1 ), as is the case for aluminum and its alloys, is bell-shaped. Studies performed in [43] show that under quasi-static loading at a given temperature, yield strength increases linearly with pressure: Y = Y 0 + αP , where Y 0 is yield strength at atmospheric pressure, and the temperature dependence can be represented as It is therefore apparent that copper undergoes greater hardening under the effect of shock waves than does aluminum.…”
Section: Coppermentioning
confidence: 99%